L’approche écologique dans les théories de l’apprentissage : une perspective de recherche concernant le « sujet-apprenant » - Fadi El Hage; Christian Reynaud (Éducation et Socialisation)
First, we situate our paper with regard to important conceptual elements issued from theories which tried to define what is a Subject. Next, we consider the Subject as a “learning-subject” and we discuss different learning approaches. We also present two central concepts to conceive the Subject from our point of view : the expansive learning and the defensive learning. We then present the theoretical bases which addressed the Subject in development in all its complexity, in particular the paradigm of complexity and the ecological approach. Lastly, we present examples of research studies which operationalize the concept of “learning-subject” within the frameworks of educations to sexuality, health, environment and citizenship.